Factors Forming The Modern World View Of Youth's (Czech Journal of Multidisciplinary Innovations, 2025)
The article discusses the factors that have a significant impact on the formation of an innovative worldview among young people. The role of the social environment, the organic cooperation of education, science and production, the system of spiritual and material values, etc. is especially emphasized.